Strength Performance of Concrete containing Date Seeds as Partial Replacement of Coarse Aggregates under the Exposure of NaCl and Na2SO4 - Adnan Ahmed; Sajjad Ali Mangi; Arslan Wali Muhammad; Naseer Ul Din (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This study aimed to investigate the strength performance of concrete containing Date Seeds (DS) exposed to Sodium Chloride (NaCl) and Sodium Sulphate Na2SO4. In this study, we have replaced the Coarse Aggregates with Date Seeds (DS) by different percentages of weight i.e. (CA:DS)%, (100:0)%, (98:2)%, (97:3)% and (96:4)%. The constant water-cement ratio was used in all mixes i.e. 0.5. Workability, Density, and compressive strength were examined by casting 48 standard cubes of 100mm size, and exposure to the NaCl and Na2SO4 Solution for curing at 7 and 28 days. Test results demonstrated that workability first increases at 2% replacement but then decreases as replacement increases. The results of Density and Compressive Strength of Cubes cured in plain water and in mixed solution of NaCl and Na2SO4 were compared. It was observed that the replacement of coarse aggregate with date seeds was increases the workability of concrete. The density and compressive strength of cubes cured in plain water decreases to a small extent. For Compressive Strength, it was observed at 28 days, that the Compressive Strength of cubes placed in normal water for curing have greater values as compare to the cubes placed in the salt solution.